2016
DOI: 10.5194/se-7-285-2016
|View full text |Cite
|
Sign up to set email alerts
|

Classification and quantification of pore shapes in sandstone reservoir rocks with 3-D X-ray micro-computed tomography

Abstract: Abstract. Recent years have seen a growing interest in the characterization of the pore morphologies of reservoir rocks and how the spatial organization of pore traits affects the macro behavior of rock-fluid systems. With the availability of 3-D high-resolution imaging, such as x-ray microcomputed tomography (µ-CT), the detailed quantification of particle shapes has been facilitated by progress in computer science. Here, we show how the shapes of irregular rock particles (pores) can be classified and quantifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Knowledge of pore/grain shape or size is essential and plays an important role in the hydromechanical behaviour and petrophysical properties of rocks (Akin et al 2009;Delle Piane et al 2015;Schmitt et al 2015;Soete et al 2015). Thus, we examined the X-ray CT images of the three samples carefully to determine the pore shape and orientations.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of pore/grain shape or size is essential and plays an important role in the hydromechanical behaviour and petrophysical properties of rocks (Akin et al 2009;Delle Piane et al 2015;Schmitt et al 2015;Soete et al 2015). Thus, we examined the X-ray CT images of the three samples carefully to determine the pore shape and orientations.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify such pore scale processes in statistical terms, timeevolving pore size distribution (PSD) was computed by using the watershed and distance transform algorithms and Avizo's XPoreNetworkModeling module [FEI Company, 2016;Rabbani et al, 2016;Schmitt et al, 2016]. To quantify such pore scale processes in statistical terms, timeevolving pore size distribution (PSD) was computed by using the watershed and distance transform algorithms and Avizo's XPoreNetworkModeling module [FEI Company, 2016;Rabbani et al, 2016;Schmitt et al, 2016].…”
Section: Evolution Of the Pore Size Distributionmentioning
confidence: 99%
“…The analyses presented in the previous sections showed that mineral precipitation results in a highly heterogeneous alteration of the microstructure. To quantify such pore scale processes in statistical terms, timeevolving pore size distribution (PSD) was computed by using the watershed and distance transform algorithms and Avizo's XPoreNetworkModeling module [FEI Company, 2016;Rabbani et al, 2016;Schmitt et al, 2016]. The size of each identified pore was reported as the diameter of a sphere having equivalent volume ( Figure S7).…”
Section: Evolution Of the Pore Size Distributionmentioning
confidence: 99%
“…2). Schlüter et al (2016) showcase the application of µ-CT imaging for the analysis soil structure deformation, whereas Schmitt et al (2016) present new research on the classification and quantification of pore shapes of reservoir rocks. Within the paper of Schoesser et al (2016), research of the penetration behavior of bentonite suspensions into noncohesive media is presented.…”
Section: Content and Highlights Of This Special Issuementioning
confidence: 99%